Self-Referential Information Alleviates Retrieval Inhibition of Directed Forgetting Effects—An ERP Evidence of Source Memory - Mao, Xinrui; Wang, Yujuan; Wu, Yanhong; Guo, Chunyan (Frontiers in Behavioral Neuroscience, 2017)
Directed forgetting assists in preventing outdated information from interfering with cognitive processing. Previous studies pointed that self-referential items alleviated directed forgetting effects due to the elaboration of encoding processes. However, the retrieval mechanism of this phenomenon remains unknown. Based on the dual-process framework of recognition, the retrieval of self-referential information was involved in familiarity and recollection. Using source memory tasks combined with ERP recording, our research investigated the retrieval processes of alleviative directed forgetting effects elicited by self-referential information. The FN400 (frontal negativity at 400ms) is a frontal potential at 300-500 ms related to familiarity and the LPC (late positive complex) is a later parietal potential at 500-800 ms related to recollection. The FN400 effects of source memory suggested that familiarity processes were promoted by self-referential effects without the modulation of TBF instruction. The ERP results of directed forgetting effects were involved with LPCs of source memory, which indexed retrieval processing of recollection. The other-referential source memory of TBF instruction caused the absence of LPC effects, while the self-referential source memory of TBF instruction still elicited the significant LPC effects. Therefore, our neural findings suggested that that self-referential processing improved both familiarity and recollection. Furthermore, the self-referential processing advantage which was caused by the autobiographical retrieval alleviated retrieval inhibition of directed forgetting, supporting that the self-referential source memory alleviated directed forgetting effects.